EFFECT ANALYSIS OF GOOD CORPORATE GOVERNANCE AND CORPORATE SOCIAL RESPONSIBILITY ON COMPANY VALUE WITH PROFITABILITY AS MEDIATION VARIABLE - Ezzi Liska Putri; Idham Lakoni; Sintia Safrianti (Faculty of Economics dan Business, Atma Jaya Makassar University, 2023)
The value of company will continue to grow when the company takes notice on economic aspect, social, and also the environment. This research aims to know whether good corporate governance and corporate social responsibility direct effect and indirect effect with profitability to company value. Population in this study were 213 manufacturing company registered in Indonesia Stock Exchange in the year of 2017-2021. Sample selection by using techniques purposive sampling with certain criteria so that the number of sample obtained 25 company that fits the criteria already determined. Data analysis used in this study namely SEM-PLS (Partial Least Square). The results of this study indicate that good corporate governance has not significant effect and positive on firm value. Good corporate governance has not significant effect and positive on profitability. Corporate social responsibility has significant effect and negative on profitability. Corporate social responsibility has not significant effect and positive on firm value. Profitability has not significant effect and negative on firm value. Indirectly good corporate governance has not significant effect to company value with profitability and indirectly corporate social responsibility also has not significant effect on firm value in the presence of profitability.